2015
DOI: 10.1111/acel.12309
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular sex steroid hormones are associated with skeletal muscle strength and power in women with different hormonal status

Abstract: Estrogen (E2)-responsive peripheral tissues, such as skeletal muscle, may suffer from hormone deficiency after menopause potentially contributing to the aging of muscle. However, recently E2 was shown to be synthesized by muscle and its systemic and intramuscular hormone levels are unequal. The objective of the study was to examine the association between intramuscular steroid hormones and muscle characteristics in premenopausal women (n = 8) and in postmenopausal monozygotic twin sister pairs (n = 16 co-twins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 29 publications
(48 reference statements)
0
37
0
Order By: Relevance
“…In fact, it has been reported that the positive effects of testosterone levels on muscle strength and physical performance are independent on its influence on muscle mass (Auyeung et al, 2011). In this sense, intramuscular androgens and estradiol levels have been proved to be significant, independent predictors of muscle strength and power in women with differential hormonal status (Pöllanen et al, 2015). Testosterone replacement therapy in men aged 61-71 years resulted in increased muscle fiber diameter and peak power, affecting mainly type I fiber peak force (Fitts et al, 2015) supporting the influence of testosterone on muscle function.…”
Section: Sex Hormonesmentioning
confidence: 99%
“…In fact, it has been reported that the positive effects of testosterone levels on muscle strength and physical performance are independent on its influence on muscle mass (Auyeung et al, 2011). In this sense, intramuscular androgens and estradiol levels have been proved to be significant, independent predictors of muscle strength and power in women with differential hormonal status (Pöllanen et al, 2015). Testosterone replacement therapy in men aged 61-71 years resulted in increased muscle fiber diameter and peak power, affecting mainly type I fiber peak force (Fitts et al, 2015) supporting the influence of testosterone on muscle function.…”
Section: Sex Hormonesmentioning
confidence: 99%
“…Testosterone (T) is an anabolic-androgenic steroid hormone that primarily interacts with androgen receptors (AR) in skeletal muscle whereas the more-potent dihydrotestosterone (DHT) primarily acts within sex-linked tissues with a possible secondary role in skeletal muscle (2) Although skeletal muscle content of DHT has been correlated to muscle strength and power (3), T replacement with and without dutasteride or finasteride (5α-reductase inhibitors) produces similar increases in lean tissue mass and muscle strength (4,5). Thus, it is currently unclear if DHT is more anabolic in skeletal muscle than T alone.…”
Section: Testosterone Signaling Pathways Responses and Adaptations mentioning
confidence: 99%
“…Cell separation studies indicate that two populations of GH cells (somatotrophs) are present, in roughly equal numbers (∼40%), in the rat pituitary gland. One population (light somatotrophs, also designated the type I cell) has densities <1.071 g/cm 3 , while the other (heavy somatotrophs, also designated the type II cell) has densities in ranges >1.071-1.085 g/cm 3 . The higher density of the type II cell is attributable to large numbers of 300 nm diameter, GH containing, cytoplasmic secretory granules.…”
Section: How Experiments With Rats Offer Clues Relevant To Human Exermentioning
confidence: 99%
“…In addition, a major cause of decreased muscle mass is an alteration in the hormonal networks involved in the inflammatory processes, muscle regeneration, and protein synthesis [32]. Estrogens help to maintain muscle mass [33], and in female patients, menopause leads to changes in the systemic steroid hormone profile from a regularly fluctuating estrogen cycle to very low estrogen levels [34]. The decreased estrogen concentrations are associated with an increase in pro‐inflammatory cytokines, such as tumor necrosis factor alpha or interleukine‐6, which might be implicated in the development of sarcopenia [34].…”
Section: Discussionmentioning
confidence: 99%
“…Estrogens help to maintain muscle mass [33], and in female patients, menopause leads to changes in the systemic steroid hormone profile from a regularly fluctuating estrogen cycle to very low estrogen levels [34]. The decreased estrogen concentrations are associated with an increase in pro‐inflammatory cytokines, such as tumor necrosis factor alpha or interleukine‐6, which might be implicated in the development of sarcopenia [34]. Furthermore, estrogen could have a direct effect on muscle mass, since skeletal muscle fibers have estrogen beta‐receptors on the cell membranes, in the cytoplasm, and on the nuclear membrane [35].…”
Section: Discussionmentioning
confidence: 99%